Protection of Encapsulated Medium Voltage Cells Against Electric Arc. (2016) - Damian, Claudiu; Tirnovan, Radu; Dumitru, Popandron; Osan, Marian
Abstract: Most defects within medium voltage cells are accompanied by the appearance of the electric arc, which causes significant damage to equipment and is a major threat to the human life. In the case of defects accompanied by a long term electric arc, dangerous injuries can occur, including the loss of life concerning operating and maintenance personnel. When the electric arc appears, it is necessary to interrupt the power supply source as soon as possible and this is easily done through the arc protection. The paper will demonstrate the possibility of Commence Light Arc |Detector (LAD) conditionality with the current from the source of the defect.